Traduction, communication et diversité linguistique dans trois communautés de pratiques religieuses au Cameroun - Michel Narcisse Ntedondjeu (Glottopol, 2022)
This article falls within the framework of critical sociolinguistics and attempts to explain how the social practice of language exposes the organization of religious communities in Cameroon and the production of essential resources for their functioning and harmony. In other words, it is about questioning the processes put in place to maintain a sense of belonging to multilingual communities. Following the presentation of the research concepts of community of practice and religious community, the analysis notably focuses on translation discourse to see the processes applied within churches and the functions and actions attributed to languages used in performing religious rites. Finally, this work examines how members of religious communities understand multilingualism and how this understanding relates to the sense of building united communities despite the diversity of their members, languages and cultures.